A Presence of the Past: The Legal Protection of Singapore’s Archaeological Heritage - LEE, Jack Tsen-Ta (Institutional Knowledge at Singapore Management University, 2013)
Singapore is not well known for its archaeological heritage. In fact, chance finds in the early 20th century and systematic archaeological excavations since the 1980s conducted at sites around the Singapore River have unearthed artefacts shedding light on the island’s early history. In addition, the value of archaeology for a deeper knowledge of Singapore’s British colonial past is increasingly being recognized. Nonetheless, Singapore law provides only a rudimentary framework to facilitate archaeological investigations and protect cultural artefacts. This article considers how the National Heritage Board Act (Cap 196A, 1994 Rev Ed), the Planning Act (Cap 232, 1998 Rev Ed), and the recent Preservation of Monuments Board Act 2009 (No 16 of 2009, now Cap 239, 2011 Rev Ed) may be strengthened in this regard.